Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.18632/oncotarget.3755
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 promotes bladder cancer growth by repressing the tumor suppressor DMTF1

Abstract: MicroRNA-155 (miR-155) is dysregulated in human cancers. In this study, we reported that miR-155 was over-expressed in bladder cancer tissues. We found that miR-155 promoted cell proliferation in vitro and tumorigenesis in vivo. MiR-155 directly reduced the expression of the tumor suppressor DMTF1. The expression of DMTF1 was decreased in bladder cancer tissues. Similar to the restoring miR-155 expression, knockdown of DMTF1 promoted cell growth and cell cycle progression, whereas DMTF1 over-expression rescued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 48 publications
(54 reference statements)
2
30
0
1
Order By: Relevance
“…Elevated expression of miR-155 has been described in multiple cancers, reflecting tumor staging, progression and treatment outcomes (61)(62)(63)(64). In accordance with expectations, miR-155 acts as a vital oncogene in GBCs, as was reported by Kono et al (43).…”
Section: Mir-21supporting
confidence: 72%
“…Elevated expression of miR-155 has been described in multiple cancers, reflecting tumor staging, progression and treatment outcomes (61)(62)(63)(64). In accordance with expectations, miR-155 acts as a vital oncogene in GBCs, as was reported by Kono et al (43).…”
Section: Mir-21supporting
confidence: 72%
“…Under hypoxic conditions, upregulated miR-155-5p was demonstrated to induce autophagy by regulating the expression of several autophagy-related genes [23]. In tumor cells, miR-155-5p functions as a promotor of proliferation in oral squamous cell carcinoma [24] and bladder cancer cells [25]. In addition, researchers have found that miR-155-5p mediates T lymphocyte differentiation [26] and inhibits cell apoptosis [27].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of p14 ARF cause cell cycle arrest and cell death in a p53-dependent manner [14]. ARF is an alternative reading frame product of the INK4a/ARF locus and is inactivated in many human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have found that tumors can occur in mice without p53 mutations or ARF deletions, further illustrating the importance of DMTF1 in the p53 pathway [12]. In cancers such as bladder cancer [14], colorectal cancer [15] and breast cancer [16], it has been reported that overexpression or knockdown of DMTF1 can inhibit or promote cancer progression. In the present study, it was confirmed that miR-6838-5p inhibits the expression of DMTF1 to promote proliferation and invasion of RCC cells by targeting DMTF1.…”
Section: Introductionmentioning
confidence: 99%